X-Ray Evaluation Of Association Of Knee Arthritis With Foot Arches - Batool, Uswah; Afsar, Rehan; Ali, Abid; Jameel, Maryam (Medical Science Journal for Advance Research, 2022)
Background: Knee arthritis is one of the most prevalent orthopedic conditions that affect people of all ages and genders. The changes in height of the medial longitudinal arch is one of the causes of knee arthritis. There is evidence that knee arthritis may be caused by flat feet. However, there isn't enough proof to support the link between knee OA and cavus foot. Objectives: The major goal of this study is to explain the association between foot arch height and knee arthritis. The other objective is to find the incidence of pes planus and pes cavus in people who have knee arthritis. Methodology: 76 individuals of middle age who had knee arthritis were included, excluded people with any surgery or fracture of the lower extremity. Footprints were taken through inkpads for measurement of the medial longitudinal arch. The feet are classified into three types on the basis of the Staheli arch index. Data on knee and foot arthritis were collected through X-Ray, proforma, and footprints. Data were analyzed by SPSS. Descriptive Analysis Cross tabulation was used to assess the association between knee arthritis and foot arches. Results: The findings of this study suggest an insignificant link between foot arch height and knee arthritis. Pes rectus was present in 56.6 percent of knee OA patients. Comparing pes planus and pes cavus, pes cavus was more common than pes planus among participants. Regardless of the height of the foot arch, the majority (57.9%) had Grade 3 knee arthritis. Conclusions: It was concluded that arch height had little to no effect on age-related knee OA. Regardless of arch height, knee arthritis was quite common in females aged 41 to 50. The majority of patients had both knees affected by OA. Patients with knee arthritis were shown to have more pes cavus than pes planus in terms of foot type but that percentage was still less than normal foot type.